Study on Immobilization Method of Two-species Mycelial Pellet for Degradation of Lignocellulose - GUO Wei; YAN Hong; PEI Lei (Journal of Harbin University of Science and Technology)
In our research，enzyme production ability of immobilization mycelial pellet was used as an index， the immobilization mycelial pellet was immobilized with lignin-degrading fungus G-13 and cellulose-degrading bacteria X10-1-2. The influence of five factors ( addition time，inoculation amount of cellulose-degrading bacteria， pH，temperature and rotational speed) to Mycelium pellet，ligninase production and cellulase production were studied. The results indicated that X10-1-2 and G-13 were added simultaneously and the inoculation amount was 20% ，pH was 5，culture temperature was 28℃，rotational speed was 160 r/min，the manganese( MnP) ; laccase ( Lac) ; lignin peroxidase( Lip) ; cellulose; hemicellulose were 31. 246 U/L; 16. 048 U/L; 157. 528 U/L; 197. 063 U/L; 215. 81 U/L，respectively. X10-1-2 and G-13 have the complementary advantage on the immobilization process，develope the synergy effects and promote the production of ligninase. The immobilization mycelial pellet was white，smooth surface，uniform size and good elasticity，which can satisfy practical needs